Xuetonglactones A–F: Highly Oxidized Lanostane and Cycloartane Triterpenoids From Kadsura heteroclita Roxb. Craib. - Shehla, Nuzhat; Li, Bin; Cao, Liang; Zhao, Jianping; Jian, Yuqing; Daniyal, Muhammad; Wahab, Atia-tul; Khan, Ikhlas A.; Liao, Duan-fang; Rahman, Atta-ur; Choudhary, M. Iqbal; Wang, Wei (Frontiers in Chemistry, 2020)
Xuetonglactones A–F (1–6), six unreported highly oxidized lanostane- and cycloartane-type triterpenoids along with 22 known scaffolds (7–28) were isolated from the stems of Kadsura heteroclita (Roxb.) Craib. Compared with previous congeners, xuetonglactone A (1), possesses an unprecedented 20,21-α-epoxide, and xuetonglactone D (4) features an unusual 19-α-hydroperoxyl moiety. The structures and the absolute configurations of the compounds were established by extensive one- and two-dimensional NMR, and electronic circular dichroism (ECD) spectroscopic analysis, with those of 1 and 5 confirmed by single-crystal X-ray diffraction technique. Compounds 1 and 2 exhibited inhibition of iNOS activity in LPS-induced macrophages with IC50 values of 22.0, and 17.0 μg/mL, respectively. While compounds 6, 7, 8, and 24 showed potent cytotoxic activities against human cervical cancer cell lines (HeLa) with the IC50 values of 4.0, 5.8, 5.0, and 6.4 μM, and against human gastric cancer cells (BGC 823) with the IC50 values of 2.0, 5.0, 2.5, and 2.0 μM, respectively. Moreover, plausible biogenetic pathways of (1-6) were also proposed.